The Effect of Stigma on Criminal Offenders' Functioning: A Longitudinal Mediational Model. Issue 2 (1st February 2016) - Moore, Kelly E.; Stuewig, Jeffrey B.; Tangney, June P.
ABSTRACT: Research has rarely considered criminal offenders' psychological responses to stigma, but these responses may significantly influence behavior after release from jail/prison. Jail inmates' perceived and anticipated stigma was assessed prior to release from jail/prison ( N = 163), and outcomes were assessed one year post-release ( N = 371). We hypothesized that perceived stigma would predict poor adjustment in several domains (i.e., recidivism, substance dependence, mental health symptoms, community adjustment) through anticipated stigma. Results showed that perceived stigma predicted worse community adjustment through anticipated stigma, and this varied by race. Results are explored from an interdisciplinary perspective.